A Analisis Faktor yang Berhubungan dengan Kepuasan Ibu Hamil pada Pelayanan Antenatal Care (K4) di UPTD Puskesmas Barambai Tahun 2025 - Amd.Keb, YUYUN SETYANINGSIH; Dewi, Vonny Khresna; Suhrawardi, Suhrawardi; Hipni, Rubiati (JURNAL KEBIDANAN BESTARI, 2025)
Abstract Pregnant women's satisfaction with antenatal care services (K4) reflects the quality of maternal health services during pregnancy. In UPTD Puskesmas Barambai, the satisfaction level of pregnant women is still below the national target. In 2023, the satisfaction rate was recorded at 46.40%, increasing to 62.90% in 2024, but still far from the national target of 90%. This study aims to analyze the factors associated with pregnant women's satisfaction with K4 services, including accessibility, service quality, health facilities, and officer communication. This study used a descriptive analytic design with a cross-sectional approach on 38 pregnant women who made K4 visits at the UPTD Puskesmas Barambai in 2025, with a total sampling technique. Data were analyzed using the chi-square test. The results showed that most respondents were 20-35 years old (76.3%), had secondary education (52.6%), and did not work (63.2%). A total of 68.4% of mothers were satisfied with the K4 service. Satisfaction was significantly associated with service quality (p=0.000) and health facilities (p=0.000), while accessibility showed a trend but was not significant (p=0.065). Mothers with close access, good service quality, complete facilities, and effective communication were more likely to be satisfied. Based on the results of the study, it can be concluded that service quality and health facilities have a significant relationship with pregnant women's satisfaction, while accessibility is not significant but still has a numerical effect. Improving the quality, completeness of facilities, and staff communication is important to support pregnant women's satisfaction and the achievement of K4 service targets. Keyword: Satisfaction, K4, Accessibility, Service Quality, Facilities, Communication.